Characterization of influenza outbreaks in Lebanon during the 2013/14 and 2014/15 seasons - Refaey, Samir; Saito, R; Akinobu, H; Shaker, R; Akel, I; Assaf-Casals, A; Lteif, M; Odagiri, T; Inaba, R; Soudani, N; Khafaja, S; Ghanem, S; et al. (Eastern Mediterranean Health Journal, 2016)
Despite the significant burden of influenza outbreaks, active disease monitoring has been largely absent in the Middle East, including Lebanon. In this study we characterized influenza virus in 440 nasopharyngeal swabs collected from patients with acute respiratory infections during two influenza seasons in Lebanon. Influenza A[H3N2] was dominant in the 2013/14 season while the A[H1N1]pdm09 and B/Yamagata strains were most prevalent in the 2014/15 season. All tested isolates were susceptible to 4 neuraminidase inhibitors [oseltamivir, zanamivir, peramivir and laninamivir]. Genetic analysis of the haemagglutinin gene revealed multiple introductions of influenza viruses into Lebanon from different geographic sources during each season. Additionally, large data gaps were identified in the Middle East region, as indicated by the lack of current influenza sequences in the database from many countries in the region Malgré la lourde charge que représentent les flambées de grippe, la surveillance active de la maladie était jusqu'à présent inexistante au Moyen-Orient, et notamment au Liban. Dans la présente étude, le virus de la grippe a été caractérisé dans 440 sécrétions rhinopharyngées prélevées par écouvillonnage chez des patients ayant souffert d'infections respiratoires aiguës pendant deux saisons grippales au Liban. Le virus de la grippe A[H3N2] était prédominant pendant la saison 2013/2014, tandis que celui de la grippe A[H1N1]pdm09 et les souches de grippe B/Yamagata étaient les plus courants pendant la saison 2014/2015. Tous les isolats testés étaient sensibles à quatre inhibiteurs de la neuraminidase [l'oseltamivir, le zanamivir, le peramivir, et le laninamivir]. L'analyse génétique du gène de l'hémagglutinine a révélé de multiples introductions des virus de la grippe au Liban, depuis différentes sources géographiques au cours de chaque saison. De plus, d'importantes lacunes dans les données ont été constatées dans la région du Moyen-Orient, comme le montre l'absence des séquences génétiques actuelles de la grippe dans les bases de données de nombreux pays de la region